Kala you know the secret now you die - Anwar, Joko; Punjabi, Dhamoo; Punjabi, Manoj; MD Pictures ([Indonesia] : MD Pictures, 2007)
A police detective named Eros investigates the death of five men who were burnt alive by a mob of pedestrians after someone screamed'thief!' at them at a bus station. While his superior orders him to lay off the'insoluble' case, Eros discovers there's a more sinister motive behind the killing than just a simple vigilantism. Meanwhile, a journalist named Janus is having the lowest time of his life. His wife divorces him and his boss fires him for a same reason. He' suffering from narcolepsy which makes him falls into a deep sleep every time he experiences a sudden emotional reaction such as anger, fear, or joy. After unsuccessfully trying to interview the wife of one of the deceased men, the woman leaves him a message which contains a dangerous secret which may become the cause of the killing. Not knowing the meaning of the message, Janus tells his friends about it. But everybody he talks to soon dies mysteriously
Title from title screen
Executive producer, Shania Punjabi
Pelakon: Fachri Albar, Shanty, Ario Bayu, Fahrani, Tip Jabrik, Yose Rizal Manua, August Melasz
DVD format
Dolby digital
With optional English or English subtitles
Keywords: Suspense in motion pictures